2024
DOI: 10.1021/acsaem.4c00069
|View full text |Cite
|
Sign up to set email alerts
|

Iron in the Presence of Iridium for Oxygen-Evolution Reaction under Alkaline Conditions

Mohammad Saleh Ali Akbari,
Subhajit Nandy,
Keun Hwa Chae
et al.

Abstract: The potential of the oxygen-evolution reaction (OER) to serve as a vital source of electrons for reducing water, carbon dioxide, and ammonia is an area of intense research. Among the numerous catalysts investigated for the OER, Ir compounds have emerged as particularly promising candidates. A notable highlight of this study is the concurrent OER activity of both Ir and Fe. Remarkably, Ir independently exhibits high OER activity, even at exceedingly low overpotentials, establishing its distinctiveness among oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…While water splitting is a promising strategy for hydrogen production, the oxygen-evolution reaction (OER) facilitated by the water-oxidation reaction remains a bottleneck. Similar to Ni/Fe, Cu/Fe-based compounds, Cu/Fe (hydr)oxides, have shown potential as effective catalysts for OER. Interestingly, some Cu complexes break down into Cu (hydr)oxide under OER conditions, which then acts as the true catalyst. The influence of Fe in the OER processes of metal oxides has also gained interest. The effect of Fe in the OER involving Ni oxide has been thoroughly investigated. , However, research on Fe’s impact on Cu (hydr)oxide OER is limited. , Indeed, the addition of a small amount of Fe ions to Cu (hydr)oxide showed high OER activity at alkaline conditions. , However, Cu (hydr)oxide tends to dissolve, complicating observations of Fe’s role. Boettcher’s research team observed that the OER performance of Fe oxide varies across different substrates, ranking from highest to lowest as Au > Pd ≈ Cu ≈ Pt > Cat at pH 14 (with pH 13 for Cu) . They attributed these differences to the variable adhesion strengths of Fe hydroxide across these substrates, suggesting that both adsorption strength and charge transport at the Fe oxide/substrate interfaces are influenced by these variations .…”
Section: Introductionmentioning
confidence: 99%
“…While water splitting is a promising strategy for hydrogen production, the oxygen-evolution reaction (OER) facilitated by the water-oxidation reaction remains a bottleneck. Similar to Ni/Fe, Cu/Fe-based compounds, Cu/Fe (hydr)oxides, have shown potential as effective catalysts for OER. Interestingly, some Cu complexes break down into Cu (hydr)oxide under OER conditions, which then acts as the true catalyst. The influence of Fe in the OER processes of metal oxides has also gained interest. The effect of Fe in the OER involving Ni oxide has been thoroughly investigated. , However, research on Fe’s impact on Cu (hydr)oxide OER is limited. , Indeed, the addition of a small amount of Fe ions to Cu (hydr)oxide showed high OER activity at alkaline conditions. , However, Cu (hydr)oxide tends to dissolve, complicating observations of Fe’s role. Boettcher’s research team observed that the OER performance of Fe oxide varies across different substrates, ranking from highest to lowest as Au > Pd ≈ Cu ≈ Pt > Cat at pH 14 (with pH 13 for Cu) . They attributed these differences to the variable adhesion strengths of Fe hydroxide across these substrates, suggesting that both adsorption strength and charge transport at the Fe oxide/substrate interfaces are influenced by these variations .…”
Section: Introductionmentioning
confidence: 99%